2015
DOI: 10.2478/raon-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Artery of Percheron infarction: review of literature with a case report

Abstract: Background.Clinical features indicating an ischemic infarction in the territory of posterior cerebral circulation require a comprehensive radiologic examination, which is best achieved by a multi-modality imaging approach (computed tomography [CT], CT-perfusion, computed tomography angiography [CTA], magnetic resonance imaging [MRI] and diffusion weighted imaging [DWI]). The diagnosis of an acute ischemic infarction, where the damage of brain tissue may still be reversible, enables selection of appropriate tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 10 publications
1
69
0
6
Order By: Relevance
“…In our study, we noted that it was only 4 of 9 in patients with bilateral infarcts, and 8 of 12 in patients with unilateral paramedian thalamic infarcts, but selective gaze palsy was not recorded. It was reported that 39.2-60% patients with bithalamic paramedian infarcts had memory impairment [12,13]. Only 1 patient with bilateral paramedian thalamic lesion in our cases complained of memory impairment, while 3 patients with unilateral lesions showed memory impairment.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our study, we noted that it was only 4 of 9 in patients with bilateral infarcts, and 8 of 12 in patients with unilateral paramedian thalamic infarcts, but selective gaze palsy was not recorded. It was reported that 39.2-60% patients with bithalamic paramedian infarcts had memory impairment [12,13]. Only 1 patient with bilateral paramedian thalamic lesion in our cases complained of memory impairment, while 3 patients with unilateral lesions showed memory impairment.…”
Section: Discussionmentioning
confidence: 54%
“…Top of basilar syndrome has a similar clinical pattern when compared with that of thalamic paramedian infarct [13]. Abnormal pupillary reflex is suggestive of the midbrain damage.…”
Section: Discussionmentioning
confidence: 94%
“…This may ultimately delay diagnosis and treatment. CT brain, especially in the acute phase, will often not identify the lesion; therefore MRI should be considered at the earliest opportunity to expedite a diagnosis, as this has a higher diagnostic yield than CT 20 23 24…”
Section: Discussionmentioning
confidence: 99%
“…Characterised by a single trunk arising from a proximal segment of either of the two posterior cerebral arteries, it supplies the paramedian thalami and the rostral midbrain bilaterally. Clinical features of AOP ischaemic stroke vary hugely due to the complex functions of the human thalamus and midbrain structures, but there are three main features: vertical gaze palsy, memory impairment and coma 2. This case report draws attention to a rare form of stroke whose presentation can mimic many other conditions, including seizures.…”
Section: Introductionmentioning
confidence: 91%